Profiling COVID-19 research in the social sciences from Indonesia based on Scopus database - Yusnaini,; Nengyanti,; Yanti, Mery; Santoso, Anang Dwi (Malaysian Journal of Library and Information Science, 2023)
This study provides insights into the pattern of COVID-19 research publications in Indonesia and aims to map out the contributions of social science scholars in the country during the pandemic, using bibliometric analysis. The analysis was conducted through desk research using the scientometric method from the Scopus database, with a total of 1,037 articles analysed. The research found that social sciences scholars in Indonesia made significant contributions to the fields of online learning, economics, business and management, public health and administration, and communication and media studies. The study also identified the influences of research areas, funding, open access, female first author, female co-authors, and international collaborative research on quartile and the number of citations. The implications of the study suggest that efforts should be made to promote gender diversity in research, allocate research funding appropriately, and encourage international collaboration. Authors should prioritize publishing in high quartile journals and opt for open access publication. Additionally, academic institutions and funding agencies should provide guidance on selecting reputable journals to maintain a culture of quality research.